MINAT SISWA DALAM Â MENGIKUTI EKSTRAKURIKULER FUTSAL STUDI PADA SISWA PESERTA EKSTRAKURIKULER FUTSAL DI SMP NEGERI 2 BUDURAN - ANGGARDI PERBOWO, DIAS (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract The improved achievement in futsal extracurricular activities in SMP Negeri 2 Buduran attract students to participate in this activity. Interest is a preferred taste and sense of attachment to a thing or activity, without any thorough. Interest is essentially the acceptance of a relationship between ourself with something outside.  The stronger the relationship, the greater the interest. An interest can be expressed through a statement that indicates that students prefer a thing to anything else, it can also be manifested through participation in an activity. Students who have an interest in certain subjects tend to give greater attention to the subject. This study aims to determine the amount of students’ interest to participate the futsal extracurricular activities in SMP Negeri 2 Buduran. Objectives of this study is the students who participate in futsal extracurricular activities in SMP Negeri 2 Buduran that amounted 30 students. The type of this research is non-experimental descriptive research with quantitative approach. The instrument of this study is interest questionnare. Conclusion: the level of students’ interest in participating the futsal extracurricular can be said to be very high with the percentage of 82.6%. The factors driving the emergence of the students’ interest in participating the futsal extracurricular is: feeling of good factor with the highest percentage value that is equal to 90.4%, then each sequence is followed by the goal factor for 85.9%, the desire factor for 83,3%, and the reason factor for 77.8% Keywords:   Interest, Student, Extracurricular, Futsal